資本市場法上 資産運用行爲規制에 關한 小考 - 정숙연(Jeong Sook-Yeon) (Tonga pŏphak, 2010)
자본시장법은 집합투자기구라는 개념을 새롭게 도입하여 집합투자에 대한규제에서 상당히 의미있는 변화를 가져왔다. 특히, 금융투자상품이라는 포괄적인 개념을 제정함으로써 투자운용의 대상도 많아졌고 집합투자제도의 구조적 특이성에서 비롯되는 대리인 문제, 즉 위임자인 투자자집단과 대리인으로서의 운용인이 엄격히 분리되어 운용인의 재량에 전적으로 의지되고 있다는점에서 그 규제의 필요성은 여전히 크다고 하겠다. 집합투자규제는 진입규제,건전성규제, 행위규제, 조직규제 등 주로 4가지로 나누어 설명할 수 있는데,특히 핵심적인 내용은 자산운용과 관련한 이해상충규제라 할 수 있다. 자본시장법에는 이해상충 행위를 직접적으로 규율하는 방식과 내부통제시스템 등의시스템규제를 하고 있으나 지면상의 문제로 본고에서는 자본시장법상 자산운용관련 행위규제를 중심으로 검토하도록 한다. 행위규제와 관련한 이해상충적 문제는 집합투자업자의 도덕적 해이를 해소하기 위한 의무의 구체화 그리고 법제도상으로 개선되어야 할 점을 함께 모색함으로써 해결할 수 있을 것이므로 본고에는 법제도상 전반의 문제점과 개선방안에 관한 몇 가지 제언을간략하게 하고자 한다. The Korean collective investment regulation is considered to be first initiated in 1961 as banks started to perform trust works under the Trust Act and Trust Business Act. However, the trust services at that time was merely a subordinate service of banks and the banks began the trust services of its actual meaning since 1969 with legislation of the Securities Investment Trust Business Act. Later the Indirect Investment Asset Management Business Act that practically consolidates the Securities Investment Trust Business Act, the Investment Company Act and other similar investment managements was enacted. In accordance with the liberalization of capital market and the trend of securitization of asset, the new act was legislated for balanced regulation on existing investment trust companies and other similar asset management activities and also to apply same act on entire indirect investment. In addition, the Capital Market Act consolidates financial instruments, defined under various acts such as the Securities and Exchange Act and the Futures Trading Act, by its function to protect investors. That is, there existed too many acts regulating capital market and the range of financial industry was excessively segmented thus its function to protect investors was hardly performed in practice because of the differences in regulative mechanisms in each financial business. The Capital Market Law was legislated to resolve such problems by revising old financial acts. The Capital Market Act introduces a new concept of collective investment scheme instead of the indirect investment from previous Indirect Investment Asset Management Business Act thus leading to a meaningful change to collective investment regulation. In the point that the number of subjects for investment management has been rapidly growing by defining the inclusive concept of financial investment instruments and that the agency problem has came into the fore since the investor group and financial manager as agency are strictly separated, the importance of regulation is not neglectable. The regulation on collective investment can be explained in context of entrance regulation, sound regulation, activity regulation and organization regulation. Especially the activity regulation, as the core content of the new act, is an activity regulation associated with conflict of interest. Although the Capital Market Act regulates the entire process through design, sales and management of fund and also the evaluation of collective investment assets, the asset management regulation can be considered as the core of conflict of interest regulation. To resolve conflict of interest, the Capital market Law provides both direct regulation on practical activities and internal control system as well. This study focuses heavily on activity regulations associated with asset management under the Capital Market Law. The Capital Market Act,compared with the previous Securities and Exchange Act, specifies the conflict of interest activities in detail. However, with a shorter history of collective investment system compare to the developed countries' cases,we still have many weak points to be improved. Thus, at this point of time, a year after the enactment of new act, it will be meaningful to review problems in system itself and interpretation of the new act. KCI Citation Count: 1